2016
DOI: 10.1371/journal.pone.0165776
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 Promotes Epithelial–Mesenchymal Transition of Endometrial Carcinoma Cells

Abstract: MicroRNA-93, derived from a paralog (miR-106b-25) of the miR-17-92 cluster, is involved in the tumorigenesis and progression of many cancers such as breast, colorectal, hepatocellular, lung, ovarian, and pancreatic cancer. However, the role of miR-93 in endometrial carcinoma and the potential molecular mechanisms involved remain unknown. Our results showed that miR-93 was overexpressed in endometrial carcinoma tissues than normal endometrial tissues. The endometrial carcinoma cell lines HEC-1B and Ishikawa wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Increasing evidence has indicated that miRNAs exert biological functions in cancer cells by suppressing the expression of target genes (31,33). Bioinformatics analysis using TargetScan indicated that PTEN may be a potential target of miR-93-5p as determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that miRNAs exert biological functions in cancer cells by suppressing the expression of target genes (31,33). Bioinformatics analysis using TargetScan indicated that PTEN may be a potential target of miR-93-5p as determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Liu et al (22) reported that 12 miRNAs were abnormally expressed in SUI, including two groups: In the upregulated group were let-7a, miR-101, miR-125b-2, miR-190b and miR-892b; in the downregulated group were miR-124, miR-330-3p, miR-485-3p, miR-517b, miR-523, miR-589, and miR-93. IN addition, miR-93 has been reported to be involved in a number of diseases and to be abnormally expressed in the progression and tumorigenesis of a number of types of cancer, including endometrial, lung, breast, hepatocellular, pancreatic, colorectal and ovarian cancer (23). However, the roles of miRNA in SUI remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that miR-93 was able to bind to CAPN2; additionally, overexpression of miR-93 decreased the expression of calpain-2, which suggested that calpain-2 may be a direct target of miR-93. As the primary components of the urethral support tissues are connective tissues which contain a large number of ECM components, and ECM metabolism is regulated by degradative enzyme matrix metalloproteinases (MMPs) (23,24), degradative enzyme inhibitors and tissue inhibitors of metalloproteinases may be altered in patients with SUI. In the present study, it was observed that MMP1 was upregulated in the vaginal wall tissues of patients with SUI and in SUI primary fibroblasts, suggesting that MMP1 may be negatively regulated by miR-93, which was consistent with a previous report (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the random effect model was selected. The overall sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and AUC were 0.76 (0.64-0.85), 0.82 (0.64-0.92), 4.2 (2.2-8.1), 0.29 (0.22-0.40), 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and 0.85 (0.82-0.88), respectively, suggesting the excellent potential diagnostic capability of miR-93 in various human cancers. Subgroup analyses based on ethnicity, sample type, and expression level were performed ( Table 2).…”
Section: The Diagnostic Meta-analysismentioning
confidence: 99%